Aerodynamic Interference between Oscillating Lifting Surfaces and Fuselage Part 2: Some Applications of Oscillating Lifting Surface Theory - Valentin Adrian Jean BUTOESCU (INCAS Bulletin, 2014)
This is the second article of a series that deals with the calculation of the aerodynamic unsteady forces on lifting surfaces. It presents some new important details on the lifting surface theory that performs oscillations in subsonic flow. These features will be applied to the aerodynamic response to certain kind of gusts and to the flapping wing calculations.